A Recombinant Human Pluripotent Stem Cell Line Stably Expressing Halide-Sensitive YFP-I152L for GABAAR and GlyR-Targeted High-Throughput Drug Screening and Toxicity Testing. - Künzel, Katharina; Friedrich, Oliver; Gilbert, Daniel (Frontiers in Molecular Neuroscience, 2016)
GABARs and GlyRs are considered attractive drug targets for therapeutic intervention and are also increasingly recognized in the context of in vitro neurotoxicity (NT) and developmental neurotoxicity (DNT) testing. However, systematic human-specific GABAR and GlyR-targeted drug screening and toxicity testing is hampered due to lack of appropriate in vitro models that express native GABARs and GlyRs. We have established a human pluripotent stem cell line (NT2) stably expressing YFP-I152L, a halide-sensitive variant of yellow fluorescent protein (YFP), allowing for fluorescence-based functional analysis of chloride channels. Upon stimulation with retinoic acid, NT2 cells undergo neuronal differentiation and allow pharmacological and toxicological evaluation of native GABARs and GlyRs at different stages of brain maturation. We applied the cell line in concentration-response experiments with the neurotransmitters GABA and glycine as well as with the drugs strychnine, picrotoxin, fipronil, lindane, bicuculline, and zinc and demonstrate that the established in vitro model is applicable to GABAR and GlyR-targeted pharmacological and toxicological profiling. We quantified the proportion of GABAR and GlyR-sensitive cells, respectively, and identified percentages of approximately 20% each within the overall populations, rendering the cells a suitable model for systematic in vitro GABAR and GlyR-targeted screening in the context of drug development and NT/DNT testin
Keywords: Gamma-aminobutyric acid receptor type-A chloride channel (GABAAR); Glycine receptor chloride channel (GlyR); Human pluripotent embryonal teratocarcinoma stem cells; NT2 cells; NT2-N cells; YFP-I152L

Establishment and validation of recombinant cell lines for high-throughput DNT testing - Künzel, Katharina; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Acta Physiologica, 2015)

Optimizing neuronal differentiation of human pluripotent NT2 stem cells in monolayer cultures. - Abolpour Mofrad, Sepideh; Künzel, Katharina; Friedrich, Oliver; Gilbert, Daniel (Development, growth & differentiation, 2016)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro developmental toxicity and neurotoxicity (DT/DNT) studies as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and allow toxicity testing at different stages of maturation. However, differentiation of NT2 cells is not straightforward. There are different protocols available in the literature reporting varying results with regard to differentiation efficiency, expression of neuronal markers and morphological characteristics of differentiated cells. Yet, the efficiency of available protocols has not been systematically compared. To address this question, we quantified the number and size of cell cluster formed during differentiation using published and modified protocols and analyzed the abundance of neuronal and non-neuronal expression markers using immunocytochemistry. In the course of the experiments we observed that differentiation results strongly depend on the cell density at differentiation-initiation as well as on the type of used cell culture plastic ware. Based on those observations and the results from our comparative analysis, we created our own optimized and robust protocol that reproducibly reveals differentiated cells with high yield. We conclude that our method may be superior to differentiation of NT2 cells for systematic in vitro-based primary screening for developmental toxicants and neurotoxicants at different stages of maturation over previous protocols used. Our approach will also contribute to reduce animal testing in the context of the 3Rs.

Phenotyping Cellular Viability by Functional Analysis of Ion Channels: GlyR-Targeted Screening in NT2-N Cells. - Künzel, Katharina; Abolpour Mofrad, Sepideh; Gilbert, Daniel (Methods in Molecular Biology, 2017)
Glycine receptor chloride channels (GlyRs) are attractive drug targets for therapeutic intervention and are also more and more recognized in the context of in vitro neurotoxicity and developmental neurotoxicity testing. Assaying the functional properties of GlyR can serve as an indicator of cellular viability and the integrity of the developing and mature central nervous system. Human pluripotent NTERA-2 (NT2) stem cells undergo neuronal differentiation upon stimulation with retinoic acid and express a large variety of neuronal proteins-including GlyR. YFP-I152L, a halide-sensitive variant of yellow fluorescent protein, allows high-throughput fluorescence-based functional analysis of GlyRs in NT2 cells. Here we describe a protocol for phenotyping of cellular viability by functional analysis of GlyR in neuronally differentiated NT2 (NT2-N) cells using YFP-I152L as a reporter of functional integrity of GlyRs. The protocol describes neuronal differentiation of NT2 stem cells, transient transfection of NT2-N cells with YFP-I152L as well as functional imaging and analysis of data from high-content imaging.
Keywords: Cell viability; Glycine receptor chloride channel (GlyR); Human pluripotent embryonal teratocarcinoma stem cells; NT2 cells; NT2-N cells; Toxicological screening; YFP-I152L

"Store-operated" and P2X-induced Ca2+ entry are differentially modulated by the antibiotic minocycline in murine BV2 microglia cells - Friedrich, Oliver; Gilbert, Daniel; Buttgereit, Andreas; Künzel, Katharina; Watson, J.; Stebbing, Martin J.; Stokes, Leanne; Adams, David J. (Wiley-Blackwell, 2015)

Store-Operated Ca(2+) Entry (SOCE) and Purinergic Receptor-Mediated Ca(2+) Homeostasis in Murine bv2 Microglia Cells: Early Cellular Responses to ATP-Mediated Microglia Activation. - Gilbert, Daniel; Stebbing, Martin J.; Künzel, Katharina; Murphy, Robyn M.; Zacharewicz, Evelyn; Buttgereit, Andreas; Stokes, Leanne; Adams, David J.; Friedrich, Oliver (Frontiers in Molecular Neuroscience, 2016)
Microglia activation is a neuroinflammatory response to parenchymal damage with release of intracellular metabolites, e.g., purines, and signaling molecules from damaged cells. Extracellular purines can elicit Ca(2+)-mediated microglia activation involving P2X/P2Y receptors with metabotropic (P2Y) and ionotropic (P2X) cell signaling in target cells. Such microglia activation results in increased phagocytic activity, activation of their inflammasome and release of cytokines to sustain neuroinflammatory (so-called M1/M2 polarization). ATP-induced activation of ionotropic P2X4 and P2X7 receptors differentially induces receptor-operated Ca(2+) entry (ROCE). Although store-operated Ca(2+) entry (SOCE) was identified to modulate ROCE in primary microglia, its existence and role in one of the most common murine microglia cell line, BV2, is unknown. To dissect SOCE from ROCE in BV2 cells, we applied high-resolution multiphoton Ca(2+) imaging. After depleting internal Ca(2+) stores, SOCE was clearly detectable. High ATP concentrations (1 mM) elicited sustained increases in intracellular [Ca(2+)]i whereas lower concentrations (≤100 μM) also induced Ca(2+) oscillations. These differential responses were assigned to P2X7 and P2X4 activation, respectively. Pharmacologically inhibiting P2Y and P2X responses did not affect SOCE, and in fact, P2Y-responses were barely detectable in BV2 cells. STIM1S content was significantly upregulated by 1 mM ATP. As P2X-mediated Ca(2+) oscillations were rare events in single cells, we implemented a high-content screening approach that allows to record Ca(2+) signal patterns from a large number of individual cells at lower optical resolution. Using automated classifier analysis, several drugs (minocycline, U73122, U73343, wortmannin, LY294002, AZ10606120) were tested on their profile to act on Ca(2+) oscillations (P2X4) and sustained [Ca(2+)]i increases. We demonstrate specific drug effects on purinergic Ca(2+) pathways and provide new pharmacological insights into Ca(2+) oscillations in BV2 cells. For example, minocycline inhibits both P2X7- and P2X4-mediated Ca(2+)-responses, and this may explain its anti-inflammatory action in neuroinflammatory disease. As a technical result, our novel automated bio-screening approach provides a biomedical engineering platform to allow high-content drug library screens to study neuro-inflammation in vitro.

Structural changes at the myrtenol backbone reverse its positive allosteric potential into inhibitory GABAA receptor modulation. - Milanos, Sinem; Künzel, Katharina; Gilbert, Daniel; Janzen, Dieter; Sasi, Manju; Büttner, Andrea; Frimurer, Thomas M.; Villmann, Carmen (Biological Chemistry, 2018)
GABAA receptors are ligand-gated anion channels that form pentameric arrangements of various subunits. Positive allosteric modulators of GABAA receptors have been reported as being isolated either from plants or synthesized analogs of known GABAA receptor targeting drugs. Recently, we identified monoterpenes, e.g. myrtenol as a positive allosteric modulator at α1β2 GABAA receptors. Here, along with pharmacophore-based virtual screening studies, we demonstrate that scaffold modifications of myrtenol resulted in the loss of modulatory activity. Two independent approaches, fluorescence-based compound analysis and electrophysiological recordings in whole-cell configurations were used for analysis of transfected cells. C-atoms 1 and 2 of the myrtenol backbone were identified as crucial to preserve positive allosteric potential. A modification at C-atom 2 and lack of the hydroxyl group at C-atom 1 exhibited significantly reduced GABAergic currents at α1β2, α1β2γ, α2β3, α2β3γ and α4β3δ receptors. This effect was independent of the γ2 subunit. A sub-screen with side chain length and volume differences at the C-atom 1 identified two compounds that inhibited GABAergic responses but without receptor subtype specificity. Our combined approach of pharmacophore-based virtual screening and functional readouts reveals that side chain modifications of the bridged six-membered ring structure of myrtenol are crucial for its modulatory potential at GABAA receptor
Keywords: allosteric modulation; GABAA receptor; myrtenol; patch clamp recording; virtual screening; YFPI152L